Towards an indicator of R&D and human development. Issue 2 (4th March 2021) - Kruss, Glenda; Sithole, Moses; Buchana, Yasser
ABSTRACT: To measure policy progress, one key science, technology and innovation indicator has long captured the imagination of policy makers: gross domestic R&D expenditure as a proportion of the gross domestic product of a country. However, African development challenges inform new policy commitments to orient STI towards inclusive and sustainable development. Such dynamics led us to question how the prevailing STI measurement frameworks need to change. A starting point is to add a complementary measure: how can existing methods be used to assess and track the gross domestic R&D expenditure oriented to drive equitable and inclusive human development? The paper aims to design such a complementary indicator using existing national R&D datasets collected in line with the Frascati guidelines. We focus our experimentation in the South African context, with a view to generalising new measures to the sub-Saharan African context over the longer term.